2020
DOI: 10.4314/jsasa.v53i1.8
|View full text |Cite
|
Sign up to set email alerts
|

The role of records management in ensuring good governance in Africa

Abstract: Proper records management is central to the promotion of good governance. Africa is a continent which has generally been riddled with poor governance. Principles of good governance such as accountability, transparency and the rule of law are ascertained with available records. Poor records management practices promote bad economic practices such as corruption and fraud. An assessment of the performance of government can thus be realised through proper records management and access to information. Good records … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 34 publications
2
23
0
Order By: Relevance
“…A study by Akporhonor (2011) found ineffective records management and recommended that state university libraries create records because of their historical, financial and evidential value. This implied that the development of a records management strategy must be based on ISO 15489 -2016 (Mosweu & Rakemane 2019). ISO 15489 -2016 emphasises linking records management strategy to legal, policy regulatory framework, an appropriate organisational structure, awareness, raising, capacity building and proper records storage.…”
Section: Measurement Of Records Management Practice Performance In Th...mentioning
confidence: 99%
“…A study by Akporhonor (2011) found ineffective records management and recommended that state university libraries create records because of their historical, financial and evidential value. This implied that the development of a records management strategy must be based on ISO 15489 -2016 (Mosweu & Rakemane 2019). ISO 15489 -2016 emphasises linking records management strategy to legal, policy regulatory framework, an appropriate organisational structure, awareness, raising, capacity building and proper records storage.…”
Section: Measurement Of Records Management Practice Performance In Th...mentioning
confidence: 99%
“…It should be noted that while Wamukoya and Mutula (2005, p. 75) highlighted the aforementioned challenges as key factors affecting the development of the ARM sector in Africa, Mosweu and Rakemane (2020) also reemphasized poor records management due to a myriad of factors including but not limited to skills, budgets and technology. The root causes of problems associated with ARM in Africa is the lack of ARM education in most HEIs.…”
Section: Archives and Records Management Educationmentioning
confidence: 99%
“…Some of these institutions have even issued fake academic degrees (Wanzala, 2017). Mosweu and Rakemane (2020) opine that corruption is a result of poor records management. Proper management of records, therefore, stands as a major step toward sealing loopholes leading to this terrible monster that can devour a society (Katekwe & Mutsagondo, 2018).…”
Section: Introductionmentioning
confidence: 99%